Anticoagulation for mechanical aortic valve replacement: an international survey. (25th November 2020) - Gupta, S; Belley-Cote, E; McEwen, C; Hou, W; Eikelboom, J; Whitlock, R
Abstract: Introduction: Mechanical valves are preferred over biologic valves in younger patients because they are more durable but require long-term anticoagulation which increases the risk of bleeding. For patients with a mechanical aortic valve, the ACCP guidelines recommend a target INR of 2.5 (range 2.0–3.0) for all patients, whereas the ACC/AHA and ESC guidelines recommend a higher target for selected patients with additional risk factors for thromboembolism (TE). Data supporting the guideline recommendations are largely historical and of low quality. Purpose: We surveyed physicians who manage anticoagulation for patient with mechanical heart valves to determine their usual practice, perceptions regarding guideline recommendations, and interest in participating in a randomized controlled trial (RCT) comparing lower with higher INR targets in patients with a mechanical aortic valve. Methods: A 33-question web-based survey was sent to 75 cardiologists, cardiac surgeons and thrombosis specialists at centres in Canada and internationally (western Europe, South America, and the United States) who participated in previous anticoagulation trials led by investigators at McMaster University. Results: Of the 55 respondents (73.3% response rate), 77.8% worked in academic teaching hospitals. Respondents had been in practice for a mean of 23.6 years; 40.9% followed AHA/ACC guidelines, 34.1% followed the ACCP guidelines and 22.7% followed the ESC guidelines. In patients with a mechanical aortic valve and no additional TE risk factors, 80% of respondents targeted an INR of 2.5 (range 2.0–3.0); among patients with additional TE risk factors, 48% targeted an INR of 2.5 (range 2.0–3.0) and 44% targeted an INR of 3.0 (range 2.5–3.5). With respect to guidelines: 57.1% of respondents agreed or strongly agreed that that the evidence for the guidelines was contemporary, 53.1% agreed or strongly agreed that the evidence was derived from patients with modern bi-leaflet mechanical valves, and 57.2% of respondents agreed or strongly agreed that the evidence was not of high quality. A majority of respondents (65.9%) reported that they would accept an increase in TE risk to reduce the risk of a major bleeding event; 86.4% are willing to randomize patients with a mechanical aortic valve to a target INR of 2.0 (range 1.5–2.5) if they had no risk factors for TE and 36.4% would randomize patients to a target INR of 2.0 with additional risk factors for TE. Conclusions: Clinicians who participated in the survey followed different guidelines and employed different INR targets for patients with a mechanical aortic valve. A majority of respondents would be willing to randomize these patients to lower INR targets. Funding Acknowledgement: Type of funding source: None